Equilibrium and kinetics studies of Direct blue 71 adsorption from aqueous solutions using modified zeolite - Nezam Mirzaei; Amir Hossein Mahvi; Hooshyar Hossini (Adsorption Science & Technology)
This study deals with the application of Iranian zeolite as a low cost adsorbent for the removal of the Direct blue 71 (DB 71) from colored solution. Important parameters including equilibrium and contact time, initial dye concentration, effect of pH, and zeolite dosage were evaluated. Maximum dye removal was obtained at about 99.8% for 25 mg/L at 120 min of equilibrium. Higher adsorption efficiency of direct dye was obtained at higher dose and acidic pH. To analyze the adsorption equilibrium and kinetic, Langmuir, Freundlich, and Temkin isotherms as well as four kinetic models encompassing pseudo first-order, pseudo second-order, intraparticle diffusion, and Elovich were evaluated. The Langmuir isotherm ( R 2  = 0.995) and pseudo second-order models, gave the best fit to equilibrium experimental data. In Langmuir analysis, the maximum adsorption capacity (q m ) by 13.66 mg/g was determined. Finally, the characteristics of zeolite including both natural and modified, such as compositions, surface morphology by X-ray diffraction technique (XRD), X-ray fluorescence (XRF), and scanning electron microscopy (SEM) were obtained. According to XRF analysis, it was demonstrated that Al 2 O 3 and SiO 2 are the most part of natural and modified zeolite. Furthermore, the clinoptilolite was determined as the significant crystalloid phase by XRD pattern.